1985
DOI: 10.2214/ajr.145.6.1249
|View full text |Cite
|
Sign up to set email alerts
|

Acute renal dysfunction after major arteriography

Abstract: The incidence of acute renal dysfunction (ARD) after major arteriography was evaluated by assessment of the change in serum creatinine in 364 patients undergoing arteriography.Major arteriography was defined as abdominal aortography, abdominal aortography with lower-extremity runoft, aortic arch studies, or aortic arch plus selective carotid angiography. The influence of the volume of contrast material received, hydration, and associated risk factors was evaluated. In the entire group, the frequency of postart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(43 citation statements)
references
References 14 publications
1
41
0
1
Order By: Relevance
“…Almost all studies mentioned pre-existing renal impairment as the first and foremost risk for contrast induced nephropathy. [11][12][13][14] In a registry from Michigan Cardiovascular consortium, it was shown that of 16,592 PCIs the incidence of CIN increased with worsening baseline renal function 15 which was also confirmed in a series of 1,826 patients. 16 Another registry study showed that the incidence of renal failure after PCI increased from 2.5% in patients with mild renal impairment (serum creatinine 1.2 -1.9 mg/dL) to 30.6% in those with more severe impairment (serum creatinine > 3.0 mg/dL).…”
Section: Discussionmentioning
confidence: 78%
“…Almost all studies mentioned pre-existing renal impairment as the first and foremost risk for contrast induced nephropathy. [11][12][13][14] In a registry from Michigan Cardiovascular consortium, it was shown that of 16,592 PCIs the incidence of CIN increased with worsening baseline renal function 15 which was also confirmed in a series of 1,826 patients. 16 Another registry study showed that the incidence of renal failure after PCI increased from 2.5% in patients with mild renal impairment (serum creatinine 1.2 -1.9 mg/dL) to 30.6% in those with more severe impairment (serum creatinine > 3.0 mg/dL).…”
Section: Discussionmentioning
confidence: 78%
“…It has already been shown that dehydration potentiates the vasoconstrictive effects of contrast media and some investigators have attempted to reduce the likelihood of contrast media induced nephropathy by pretreatment with volume expansion or diuresis [17,21]. Intravenous fluid could be beneficial before the administration of contrast agents by correcting plasma volume depletion [2,8,18], but Charles et al proposed that hydration with intravenous saline before and after the procedure was not related to the development of nephropathy [3]. Mannitol with efficacy in preventing or reducing the severity of ischemic renal insufficiency in humans is also controversial [2].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, another early study on 364 patients undergoing angiography did not find a preventive effect of hydration on CIN. 35 Should fluids be administered intravenously or orally? On the one hand, Trivedi et al 36 compared the effects of intravenous normal saline at a rate of 1 mL/kg per hour for 24 hours beginning 12 hours before contrast administration versus hydration with unrestricted oral fluids on the incidence of CIN.…”
Section: Evidence For Periprocedural Hydrationmentioning
confidence: 99%